IS SYSTEMATIC VACCINATION OF GIRLS-ADOLESCENTS AGAINST HUMAN PAPILLOMA VIRUS NECESSARY? - G. N. Minkina (Вопросы современной педиатрии, 2011)
World Health Organization and European Center of Prophylaxis and Control over Morbidity recommend inclusion of systematic vaccination against human papilloma virus in girls-adolescents in national immunization programs. The article makes a review of vaccination reasonability as in countries with developed programs of neck of uterus cancer, as in societies with absence of adequate screening. Author discusses the age of vaccination and presents a foreign experience of vaccine against human papilloma virus inclusion into National Immunization Programs.